Chapter «Odyssey» Scientific Debate: Rhetoric and STEM Education - Egglezou, Foteini (Communication and Philosophical Cultures. Researches and Instruments, 2021)
Τhe Erasmus+ KA2 Odyssey project aims at introducing debates on STEM topics in European schools for cultivating the scientific, argumentative and critical literacy as well as the communication skills of students in secondary education (13-19 years old). In Greece, the testing phase (October 2019-June 2020) involved 18 STEM educators and 126 students from 11 schools. The debate format, which combined elements of Oxford and Public Forum, aimed at making students realize that scientific ideas and practices are not absolute, objective and immutable and therefore require discussions based on convincing arguments supported by relevant and sufficient evidence. The first findings of the project were encouraging, revealing that the rhetorical turn in the teaching of science through debates is purposeful for promoting advances in the modern STEM classroom despite the barriers that hinder analogous efforts.